Cyprus and its Regiment in the Second World War - Siammas, Marios (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book explores the role of the Cyprus regiment, a military unit of the British Army, in the Second World War. Highlighting the contribution of Cyprus to the war effort, the book contributes to the limited historiography on the military engagement of Cyprus in the Second World War. Through an analysis of British official records and interviews the author aims to provide the required chronological and contextual placement of events involving Cyprus and the Cyprus Regiment. By drawing upon veterans' narratives and operational insights, the book offers a personal view and assessment of the Second World War period. The book covers a number of themes, including the recruitment of Cypriots to the British Army and the training they received, the establishment of the Cyprus Volunteer Force, the experiences of Cypriot soldiers while serving in multiple countries, and the wider impact of the war on Cyprus, economically, socially and militarily. Marios Siammas has worked at the British High Commission Nicosia since June 2023. Previously he held the position of Researcher at the Committee on Missing Persons in Cyprus. He is also an independent historian and studied at Panteion University of Social and Political Studies, Athens, Greece, and Brunel University of West London, UK, before completing his PhD in Defence Studies at King's College London in the UK. He has mostly published on the Cypriot contribution to the Second World War and the modern history of Cyprus.
Chapter 1: Introduction -- Chapter 2: Recruitment, Training and Initial Deployment -- Chapter 3: Cyprus Volunteer Force: Local Forces In Defence of The Island -- Chapter 4: In Defence of Cyprus: The British Floating Fortress in the Eastern Mediterranean? -- Chapter 5: Cypriots Fight for the Allied Cause: The Experience Abroad -- Chapter 6: The War Comes to an End: The Demobilisation of Cypriot Volunteers -- Chapter 7: The Impact of War on Cyprus: During and After the War -- Chapter 8- Conclusion. .
Keywords: Europe -- History; Military history; Imperialism; Great Britain -- History; World War, 1939-1945.; European History; Military History; Imperialism and Colonialism; History of Britain and Ireland; History of World War II and the Holocaust